Role of pelareorep in activating anti-tumor immunity in PDAC - Vile, Richard; Siveke, Jens T.; Liffers, Sven-Thorsten; Heineman, Thomas Charles; Coffey, Matt (Journal of clinical oncology, 2025)
2562Background: Pancreatic ductal adenocarcinoma (PDAC) is highly lethal cancer with limited immunotherapeutic options. Pelareorep (pela) is an intravenously delivered unmodified reovirus containing a double stranded RNA genome that has been studied as an immunotherapeutic in multiple cancers including breast, anal, colorectal and pancreatic. We previously reported high tumor response rates in first-line metastatic PDAC patients treated with pela combined with gemcitabine, nab-paclitaxel and atezolizumab. We report here the immunologic effects of pela in a cohort of first-line metastatic PDAC subjects treated with pela plus chemotherapy and atezolizumab and the correlation of these effects with tumor response. Methods: To examine its effects on pancreatic cancer, a phase 1/2 Simon 2-stage platform study (GOBLET) was performed that included patients with first-line locally advanced/metastatic unresectable PDAC. Anti-reovirus T cell activity was assessed by interferon gamma secretion (ELISPOT). Changes in the expression of plasma proteins were analyzed by Olink Response panels. T cell receptor sequencing (TCR-seq; ImmunoSEQ Assay, Adaptive Biotechnologies) was performed on tissue collected prior to the start of therapy and on blood from baseline through 3 treatment cycles to identify TILs expansion. Tumor responses were scored according to the modified RECIST v1.1 criteria. Results: Increases in anti-reovirus T cell activation as determined by ELISPOT after cycle 3 of therapy were observed in 6/8 subjects. Three subjects with maximum responses (> 300 spots) showed >30% decreases in tumor volume. Significant changes in plasma proteins as determined by Olink included PD-L1, CXCL9, CXCL10, CXCL11 and IFN-γ. Pre-treatment tumor tissue was used to identify the TIL clonal populations prior to therapy. Increased TIL clones in the blood pre-treatment was associated with tumor responses. Pela treatment increased the expansion of pre-existing and new TIL clones in the blood after one cycle of treatment. Sustained increases in pre-existing TIL clonal populations in the blood through cycle 3 of therapy were observed in subjects who exhibited reductions in tumor volume. Conclusions: These findings, while preliminary, demonstrate that pela induces not only anti-reovirus T cells but also activates innate and adaptive anti-tumor immunity in PDAC subjects treated with chemotherapy and atezolizumab. Tumor responses are associated with both the presence of TIL clones in the blood prior to treatment and the expansion of pre-existing TILs in the blood on treatment. These findings provide additional insights into the immunologic mechanisms by which pela-based therapy may provide clinical benefit in patients with metastatic PDAC.